Dysregulation of innate immune receptors on neutrophils in chronic granulomatous disease - Hartl, Dominik; Lehmann, Natalie; Hoffmann, Florian; Jansson, Annette; Hector, Andreas; Notheis, Gundula; Roos, Dirk; Belohradsky, Bernd H.; Wintergerst, Uwe (Journal of allergy and clinical immunology, 2008)
Chronic granulomatous disease (CGD) is the most common inherited disorder of neutrophil function, is caused by mutations in the reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, and results in recurrent bacterial infections. We sought to investigate the expression and function of innate immune receptors on neutrophils in patients with CGD. We quantified mRNA and protein expression of Toll-like receptors (TLRs), complement receptors, and chemokine receptors on neutrophils from 15 patients with CGD compared with that seen in healthy control subjects (n = 15) and control patients with bacterial pneumonia (n = 15). Phagocytosis, chemotaxis, and TLR function of isolated neutrophils were analyzed. The effect of NADPH oxidase inhibition on receptor expression and function was analyzed in control neutrophils. Neutrophils from patients with CGD had lower expression levels of TLR5, TLR9, CD11b, CD18, CD35, and CXCR1 compared with those from healthy control subjects, whereas similar or increased receptor expressions were found in patients without CGD but with bacterial pneumonia. Reduced TLR5 expression resulted in impaired neutrophil activation by bacterial flagella, reduced CD11b/CD18 expression was associated with impaired phagocytosis of Staphylococcus aureus, and reduced CXCR1 expression was associated with decreased chemotaxis. TLR5 and CD18 expression levels correlated with disease severity in patients with CGD. TLR5 and TLR9 expression were greater in patients with residual NADPH oxidase activity. Inhibition of the NADPH oxidase in control neutrophils in vitro decreased TLR5 and TLR9 expression and impaired TLR5 function. These results provide the first evidence that innate immune receptors are dysregulated in patients with CGD.